2001
DOI: 10.1542/peds.107.6.e92
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Dieting Behavior in Cystic Fibrosis

Abstract: ABSTRACT. Objective. To examine the relationship between pulmonary function, nutritional status, body image, and eating attitudes in children with cystic fibrosis (CF) compared with healthy controls.Method. Seventy-six children with CF (39 girls) and 153 healthy control children (82 girls) were recruited. All children were between 7 and 12 years of age. After being weighed and measured, participants undertook a structured 1-to-1 interview. Four measures were used to assess body image: body size (perception and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
3
21
1
Order By: Relevance
“…That is, the measure will be helpful in identifying any disturbance in EABs associated with weight loss or low weight maintenance in people with CF, given the negative health implications of this. The low prevalence of disturbed EABs found within this community CF sample is also consistent with the lower prevalence of EDs [1] and disturbed EABs [2,4,5] found in CF compared to control samples.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…That is, the measure will be helpful in identifying any disturbance in EABs associated with weight loss or low weight maintenance in people with CF, given the negative health implications of this. The low prevalence of disturbed EABs found within this community CF sample is also consistent with the lower prevalence of EDs [1] and disturbed EABs [2,4,5] found in CF compared to control samples.…”
Section: Discussionsupporting
confidence: 85%
“…Eating disorders (EDs) or disturbed eating attitudes or behaviours (EABs) have been reported in young people [1][2][3] and adults [4][5][6] with Cystic Fibrosis (CF) and may contribute to poor nutritional status, which is associated with poor growth and delayed puberty [7], reduced lung function [8] and decreased survival [9]. It will be valuable to assess disturbances in EABs in the CF population; however, existing self-report measures of disturbed EABs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Girls scored higher than boys, which could be explained by the fact that girls are less or feel less ‘pushed’ into eating than boys; in media and fashion magazines girls are often illustrated as thin and skinny. Truby and Paxton (2001) reported similar results and concluded that adolescent girls with CF are generally not unhappy with their posture and do not necessarily wish to be any fatter and may not be motivated to eat the high‐energy diet recommended.…”
Section: Discussionmentioning
confidence: 77%
“…Overall, children had a favourable body image (median HRQOL score of 88.9). Probably, most children did not consider themselves as ‘too thin’, but rather slender as compared to their peers, which may have contributed to their overall satisfaction with body image [30]. The HRQOL scores on the domain of body image decreased with age, after adjustment for sex.…”
Section: Discussionmentioning
confidence: 99%